2012
DOI: 10.1007/s10658-012-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Mycosphaerella graminicola and Quinone Outside Inhibitor (QoI) resistance in the Czech Republic

Abstract: Damage caused by the wheat pathogen Mycosphaerella graminicola increased rapidly during the last two decades in the Czech Republic. We collected isolates from naturally infected fields in seven wheat-growing locations and analysed these using eight microsatellite markers. All markers were highly polymorphic. We found a high degree of genetic diversity and low clonality within all sampled Czech populations. We identified 158 unique multilocus haplotypes among 184 isolates. Field populations showed weak genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The same result was reported initially for Z. tritici in Tunisia (Boukef et al, 2012) and Morocco (Siah et al, 2014). However, the frequency of the G143A substitution in Z. tritici increased dramatically soon after deploying QoI fungicides in Europe (Torriani et al, 2009a;Drabe sov a et al, 2013), and the early emergence of QoI resistance has recently been reported in both Morocco (Siah et al, 2014) and Tunisia (Taher et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…The same result was reported initially for Z. tritici in Tunisia (Boukef et al, 2012) and Morocco (Siah et al, 2014). However, the frequency of the G143A substitution in Z. tritici increased dramatically soon after deploying QoI fungicides in Europe (Torriani et al, 2009a;Drabe sov a et al, 2013), and the early emergence of QoI resistance has recently been reported in both Morocco (Siah et al, 2014) and Tunisia (Taher et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…A detailed description of the sampling system and results of genetic diversity studies using microsatellite markers are available in Drabešová et al (2013). The basic criteria for the selection of 10 isolates examined here were the results of pathogenicity studies, differences in geographical origin, results of genetic diversity studies, fungicide (QoI) resistance, as well as sporulation and development of culture media.…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…Since yield losses can reach in susceptible wheat cultivars 30-40% (Šíp et al 2014), it is a major reason for fungicide applications. Since the early 2000s, however, European isolates are increasingly resistant to strobilurins (Torriani et al 2009;Drabešová et al 2013) and a shift towards higher tolerance to azoles occurs (Cools & Fraaije 2008). Hence, the use of resistant cultivars is seen as a very important method of control (Brown et al 2001;Schilly et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fungicide use to control STB exerts strong directional selection for fungicide resistance, and favors a rapid increase in the frequency of fungicide-resistant phenotypes. Since the introduction of strobilurin fungicides to control STB in the 2000s, a mutation conferring nearly complete resistance to strobilurins has been detected in the United Kingdom, United States, Czech Republic, Morocco, Ireland, France, Germany, and Denmark (Fraaije et al 2005, Gisi et al 2005, Drabešová et al 2013, Estep et al 2013, Siah et al 2014. This mutation is a single base pair substitution in the mitochondrial gene encoding cytochrome B, where glycine replaces alanine at 143 (G143A; Gisi et al 2002).…”
mentioning
confidence: 99%